Science literacy and skills of physics education students by developing a project-technology skills learning model - Fahrudin, Ahmad; Maison, Maison; Purwaningsih, Sri; Marzal, Jefri (Journal of Education and Learning (EduLearn), 2025)
This study aims to develop a learning model that can foster science literacy skills by involving ‘the ability to think critically, think creatively, and collaborate skills. Three research questions were asked: i) how to develop learning models to cultivate skills (science literacy, critical thinking, creative thinking, and collaboration); ii) how to validate it; and iii) how critical thinking, creative, and collaboration skills affect science literacy skills. This research uses analysis, design, development, implementation dan evaluation (ADDIE) development design by using validation sheets as data collection instruments: three learning model experts and two lecturers who teach introductory physics courses as practitioners participated in this research. The collected data is analyzed using V-Aiken to determine the level of validity. Overall, the validation results from model development are in the “meet requirements” and “feasible” categories for implementation. The analysis results of the relationship of research variables show that critical thinking, creative thinking, and collaboration directly affect science literacy skills; however, critical thinking and creative thinking skills have a moderate effect on science literacy skills if collaboration skills act as mediation.